Arte e interação: linguagem e produção de significado - Fogliano, Fernando (Escola de Comunicações e Artes da Universidade de São Paulo, 2015)
ABSTRACT This study seeks to deepen the understanding of the interactive processes in the field of technological art. For it will fetch in the studies of George Lakoff and Mark Johnson the elements needed to produce a perspective able to offer a deeper understanding of the processes involved in the production of meanings and aesthetic experience.

RESUMO Este estudo busca aprofundar o entendimento dos processos interativos no campo da arte tecnológica. Para isso, vai buscar nos estudos de Mark Johnson e George Lakoff os elementos necessários para a produção de uma perspectiva capaz de oferecer um maior aprofundamento sobre os processos que envolvem a produção de significados e a experiência estética.
Art and interaction: language and production of meaning
Keywords: art; interaction; language; technology; evolution; arte; interação; linguagem; tecnologia; evolução